The macrovertebrate fossil assemblage from the Name Chamber, Sterkfontein: taxonomy, taphonomy and implications for site formation processes - Val, Aurore; Stratford, Dominic J (My University, 2015)
The Name Chamber contains some of the deepest fossiliferous deposits in the Sterkfontein Caves, at ~20 metres below the surface deposits of Members 4 and 5. Recent excavations complemented by detailed studies of the geological context, as well as of the microfaunal and lithic (i.e. Oldowan artefacts) assemblages, have shed some light on the complex history of sediment accumulation in that part of the Sterkfontein karstic system. The Name Chamber has a long and intricate history of deposition that is of particular value for understanding the redistribution of Oldowan-bearing sediments from Member 5 into the deep chamber below. Recognizing sediment movement and sources through multidisciplinary investigations is of key importance to reconstructing primary lithic assemblages and ultimately the behavioural proxies associated with them. Here, we present the results of a taxonomic and taphonomic analysis of the macrofaunal assemblage recovered during excavations of the decalcified sediments of the Western Talus in the Name Chamber. The taxonomic composition of the faunal spectrum is similar to that of Member 5 East Oldowan, with an overrepresentation of medium-sized bovids and the occurrence of taxa associated with grasslands. The taphonomic features of the fossil remains are characteristic of a mixed assemblage with indications of contributions by carnivores, slope wash and gravity collecting bones from the catchment surface (including carnivore-gnawed and butchery-marked specimens). The results independently corroborate lithic and microfaunal analyses and support the hypothesis of multiple origins for the sediments of the Name Chamber, with a main contribution from Member 5 East Oldowan (notably illustrated in the Name Chamber assemblage by the identification of several cut-marked remains and a bone tool), shortly after it accumulated at about 2.18 Ma. There is also indication of a minor contribution from Member 4 but no evidence for a noticeable contribution from Post-Member 6 (L/63 Infill).
Keywords: Sterkfontein Caves; Name Chamber; cave taphonomy; faunal analysis; Plio-Pleistocene; early hominins